Manajemen Pendidikan Islam Dalam Membentuk Kedisiplinan Peserta Didik - Ani Fatimatuz Zahroh Hartin Pertiwi; Abu Darim (THE JOER: Journal Of Education Research, 2022)
The purpose of this study is to analyze: (1) Islamic education planning in shaping the discipline of students; (2) organizing Islamic education in shaping the discipline of students; (3) the implementation of Islamic education in shaping the discipline of students; (4) supervision of Islamic education in shaping the discipline of students at MA Maarif Sukorejo. This research uses a qualitative research approach with a qualitative descriptive research design. The data collection techniques used are interviews, observations, documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of this study are (1) Islamic education planning in shaping the discipline of students: order planning carried out by stake holders and socialized to students. (2) The organization of Islamic education in shaping the discipline of students, the head of the madrasa appoints several teachers or staff who are given additional tasks to organize and are responsible for the smooth running of disciplinary activities that have been planned to run well. (3) The implementation of Islamic education in shaping this discipline, namely all parties, all madrasah stakeholders, especially the object, namely students and those who set an example are teachers and staff in madrasas. (4) Supervision of Islamic education in shaping the discipline of students in Maarif Sukorejo Maarif Makorejo is carried out by the committee, the head of the madrasa, and the student affairs, the homeroom teacher and the BK.